The efficacy and safety of Yupingfengsan in the treatment of allergic rhinitis: a systematic review and meta-analysis - Wang, Yi; Tang, Yumei; Xu, Jili; Bu, Yangziting; Luo, Lan; Wu, Jie (Frontiers in Pharmacology, 2025)
BackgroundAllergic rhinitis (AR) is a chronic, non-infectious inflammation of the nasal mucosa, primarily mediated by immunoglobulin E (IgE) following allergen exposure in atopic individuals. Yupingfengsan (YPFS), a classical traditional Chinese medicine (TCM) formula, has been used to manage AR. However, its efficacy and safety require comprehensive evaluation.MethodsThis review was registered in PROSPERO (CRD420251009897). Eight databases were systematically searched up to December 2024 for randomized controlled trials (RCTs) evaluating YPFS for AR. Meta-analyses were conducted using Review Manager 5.4 and Stata 18.0. Subgroup and sensitivity analyses explored heterogeneity and result stability. Publication bias was assessed using funnel plots and Egger’s test. Evidence quality was appraised with GRADEpro, and potential mechanisms of YPFS in AR were summarized.ResultsThirty-nine RCTs involving 4,578 participants met the inclusion criteria. YPFS combined with conventional pharmacotherapy significantly improved Total Nasal Symptom Score (TNSS), regulated Th1/Th2 and Treg/Th17 balance, and reduced serum IgE, IL-4, and IL-6 levels compared with conventional pharmacotherapy alone. As monotherapy, YPFS improved TNSS and lowered IgE, IL-4, and IL-6 levels more effectively than conventional treatment, though its effects on immune balance and IL-4 modulation remain uncertain due to limited data. Both regimens increased overall clinical effectiveness and reduced relapse rates. No specific adverse reactions to YPFS were reported in studies that monitored safety; however, many trials did not report adverse events, limiting conclusions about its safety profile and long-term tolerability.ConclusionYPFS, particularly when combined with conventional pharmacotherapy, offers superior benefits over conventional treatment alone in modulating immune function, reducing inflammation, improving clinical outcomes, and lowering relapse risk in AR. YPFS monotherapy also shows potential immunomodulatory and anti-inflammatory effects. Current safety data do not indicate major concerns, but incomplete reporting and limited immune parameter data restrict definitive conclusions. High-quality, rigorously monitored RCTs are needed to confirm these findings and better define the safety of YPFS in clinical use.Systematic Evaluation Registryhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251009897. Identifier [CRD420251009897].